Listening skills : resources and activities for teaching effective listening - Ryan, Kevin; Pauley, Adrian (Albert Park, Vic. : Phoenix Education, 2002)
A resource book for teachers providing information, strategies, ideas and activities for teaching listening skills to students in Years 7 to 11. Included with the book is a 36 track audio CD with material which helps explain some of the concepts in the book and which is used as the basis of some of the exercises and activities.
No system requirements available for CD-ROM component.
No system requirements available for CD-ROM component.
Keywords: Comprehension -- Study and teaching (Secondary); English language -- Spoken English -- Study and teaching (Secondary); Listening -- Study and teaching (Secondary)